2022
DOI: 10.3390/cells11142177
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs as Promising Translational Strategies for Neuronal Repair and Regeneration in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) represents a devastating injury to the central nervous system (CNS) that is responsible for impaired mobility and sensory function in SCI patients. The hallmarks of SCI include neuroinflammation, axonal degeneration, neuronal loss, and reactive gliosis. Current strategies, including stem cell transplantation, have not led to successful clinical therapy. MiRNAs are crucial for the differentiation of neural cell types during CNS development, as well as for pathological processes after ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…miRNA-based therapies face numerous challenges, including delivery, stability, and immune responses ( Hydbring and Badalian-Very, 2013 , Sun et al, 2018 ). Exposed miRNAs are difficult to be absorbed by cells due to their negative charge, off-target effect, short half-life in the systemic circulation, and rapid degradation or inactivation by abundant nucleases in the bloodstream ( Silvestro and Mazzon, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-based therapies face numerous challenges, including delivery, stability, and immune responses ( Hydbring and Badalian-Very, 2013 , Sun et al, 2018 ). Exposed miRNAs are difficult to be absorbed by cells due to their negative charge, off-target effect, short half-life in the systemic circulation, and rapid degradation or inactivation by abundant nucleases in the bloodstream ( Silvestro and Mazzon, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have addressed small EVs contributions to nerve regeneration ( Figure 3 ). Studies performed to date have shown M2 macrophages, MSCs, Schwann cells, microglial, neurons, sensory neurons, motor neurons, and astrocytes secrete small EVs, and that small EVs also contain various miRNAs ( Qing et al, 2018b ; Zhang et al, 2018 ; Silvestro and Mazzon, 2022 ). Zhang et al ( Santonocito et al, 2014 ) reported that migration and proliferation were promoted when small EVs containing miR-223 were secreted by M2 macrophages co-cultured with Schwann cells and that Schwann cell migration and proliferation were reduced when they were incubated with miR-223-inhibited M2 macrophages.…”
Section: Therapeutic Potential Of Small Evs For Improving Neural Stru...mentioning
confidence: 99%
“…Activated microglia promote secondary tissue damage in SCI. Similarly, miRNAs have been implicated in the modulation of microglial activation and polarization in SCI [ 153 ]. miR-124 is a well-studied miRNA that regulates microglial response after SCI.…”
Section: Introductionmentioning
confidence: 99%